The Crusade of the Pen: Developed During the Colonial Period and Dismantling the Discourse of the War on Terror - Meyler, Ruairí (International journal of Asian christianity, 2022)
In March 2021, Pope Francis visited Iraq, highlighting the challenges faced by the Christian community in Iraq and meeting with the Shia cleric Grand Ayatollah Ali al-Sistani. By engaging in this interreligious dialogue with al-Sistani, Pope Francis reminded us of another interreligious episode from the Crusades between Saint Francis and Sultan al-Kamil and challenged our perspective on the Crusades. This paper submits that in order to facilitate the repairing of relations between Christian and Muslim communities in the Middle East, we must dismantle the War on Terror discourse and in particular the nineteenth century Crusader images that underpin it and follow the example of Pope Francis in recovering not only a more ecumenical vision of the Crusades but also of the relationship between Middle Eastern Christians and Muslims. This article aims to dismantle this discourse which divides Muslim and Christian communities both in the West and in the Middle East by examining the use of Crusader imagery from Napoleon’s invasion of Egypt to the present, arguing that our modern images of the Crusades are developed in the eighteenth, nineteenth and early twentieth centuries, and it is these ahistorical images that also fuel the rhetoric surrounding the War on Terror.